Penerapan Layanan Konseling Kelompok dengan Teknik Self-Regulated Learning untuk Meningkatkan Disiplin Belajar Siswa Kelas X Di SMA - Yuliana La bi Longse; Anjelin Anjelin; Novita Rupang Mangayun (Pengharapan : Jurnal Pendidikan dan Pemuridan Kristen dan Katolik, 2026)
This study investigates the effectiveness of implementing group counseling services using self-regulation learning strategies to improve students' learning discipline. Learning discipline plays a crucial role as a determining factor of academic success; nevertheless, many senior high school students still demonstrate weaknesses in managing their time and fulfilling their academic responsibilities. This study adopted a quantitative approach through a quasi-experimental method utilizing a pre-test and post-test control group design. Subjects were selected using purposive sampling technique with low learning discipline scores as the primary selection criterion. Data were collected using a learning discipline scale that had been tested for its validity and reliability. Hypothesis testing was conducted through a paired sample t-test to detect changes occurring before and after the intervention was administered. The results demonstrated a meaningful improvement in students' learning discipline following participation in group counseling sessions incorporating self-regulation strategies. This technique proved beneficial in helping students plan, monitor, and evaluate their learning activities in a more structured manner. These findings suggest that incorporating self-regulation learning into group counseling has strong potential to become a leading strategy for school counselors in enhancing student discipline and academic achievement.